Severe Bradycardia Leading to Hemodynamic Instability Associated with Remdesivir Use in a Patient with COVID-19 Pneumonia - Bhargavi Donepudi; Shikhar Agarwal; Lokendra Thakur (Case Reports in Critical Care)
Remdesivir (RDV) is an approved treatment for hospitalized patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. There is limited literature on the cardiac adverse effects of RDV. We report a case of a patient who developed hemodynamically unstable bradycardia after the initiation of RDV that resolved after discontinuing RDV.